2016
DOI: 10.1002/chem.201600740
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Activation of α,β‐Unsaturated Amides: Catalytic Asymmetric Vinylogous Conjugate Addition of Unsaturated γ‐Butyrolactones

Abstract: Although catalytic asymmetric conjugate addition reactions have remarkably advanced over the last two decades, the application of less electrophilic α,β-unsaturated carboxylic acid derivatives in this useful reaction manifold remains challenging. Herein, we report that α,β-unsaturated 7-azaindoline amides act as reactive electrophiles to participate in catalytic diastereo- and enantioselective vinylogous conjugate addition of γ-butyrolactones in the presence of a cooperative catalyst comprising of a soft Lewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The 7‐azaindoline amides are characterized by their intrinsic stability and acquired reactivity in the presence of suitable Lewis acids, which is ascribed to a conformational change in the amide geometry; the stable E ‐conformer is switched to a Z ‐conformer via bidentate coordination (Figure ). The activated Z ‐conformer elicits acquired reactivity to allow for catalytic enolization (nucleophilic activation) and also serves as a Michael acceptor when conjugated with a double bond (electrophilic activation) . Given the electrophilic activation mode of the α,β‐unsaturated amide by Lewis acids, we began screening chirally decorated Lewis acidic catalysts for a 1,3‐DC reaction of amide 1 a and nitrone 2 a (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The 7‐azaindoline amides are characterized by their intrinsic stability and acquired reactivity in the presence of suitable Lewis acids, which is ascribed to a conformational change in the amide geometry; the stable E ‐conformer is switched to a Z ‐conformer via bidentate coordination (Figure ). The activated Z ‐conformer elicits acquired reactivity to allow for catalytic enolization (nucleophilic activation) and also serves as a Michael acceptor when conjugated with a double bond (electrophilic activation) . Given the electrophilic activation mode of the α,β‐unsaturated amide by Lewis acids, we began screening chirally decorated Lewis acidic catalysts for a 1,3‐DC reaction of amide 1 a and nitrone 2 a (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Shibasakia nd co-workersr eported that non-heteroaromatic 7-azaindoline amides 54 conjugated with an unsaturated bond, as discussed in Section 2.4 for nucleophilic (deprotonative) activation, served as suitable substrates for electrophilic activation (Scheme13). [32] In addition to the solid state, 54 also preferred the E conformation in solution, as indicated by the unusually downfield-shifted signalf or the a-proton in the 1 HNMR spectrum, which was due to the hydrogen-bondingi nteraction with the pyridyln itrogen of the 7-azaindoline. The conformational change to Z,d riven by the formation of the Cu I complex 55 through ab identate conformation,w as traced by 1 HNMR spectroscopy and X-ray crystallography.T hist ype of complexation is reminiscent of the activation mode of the 7-azaindoline amide, as discussed above, and the enhanced electrophilicity at the b-carbonw as evidenced by smooth and highly stereoselective conjugatea ddition of butenolides 56.…”
Section: Enantioselective Càcb Ond Formation Ofmentioning
confidence: 97%
“…The choice of chiral phosphine ligands enabled access to the products 59 and 60 bearing quaternary and tertiarys tereogenic centers. [32] The catalyst loading could be reduced to as little as 0.1 mol %, suggesting little product inhibition to disturb the catalysis.…”
Section: Enantioselective Càcb Ond Formation Ofmentioning
confidence: 99%
“…In contrast, non‐heteroaromatic amides are poorly reactive due to the attenuated polarity of the carbonyl group resulting from amide conjugation. Shibasaki and co‐workers reported that non‐heteroaromatic 7‐azaindoline amides 54 conjugated with an unsaturated bond, as discussed in Section 2.4 for nucleophilic (deprotonative) activation, served as suitable substrates for electrophilic activation (Scheme ) . In addition to the solid state, 54 also preferred the E conformation in solution, as indicated by the unusually downfield‐shifted signal for the α‐proton in the 1 H NMR spectrum, which was due to the hydrogen‐bonding interaction with the pyridyl nitrogen of the 7‐azaindoline.…”
Section: Enantioselective C−c Bond Formation Of Non‐heteroaromatic αmentioning
confidence: 99%
“…The active carbon nucleophile was generated in situ by the coexisting Brønsted base catalyst (Barton's base). The choice of chiral phosphine ligands enabled access to the products 59 and 60 bearing quaternary and tertiary stereogenic centers . The catalyst loading could be reduced to as little as 0.1 mol %, suggesting little product inhibition to disturb the catalysis…”
Section: Enantioselective C−c Bond Formation Of Non‐heteroaromatic αmentioning
confidence: 99%